Sundanese Language Variations on Children’s Speech Found in Multicultural Environment - Prihandini, Asih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Language used in multicultural environment has been analyzed and showed many new findings. This study was purposed to examine Sundanese language variations on children’s speech found in multicultural environment, especially who live in Bandung, West Java. Obtaining data were done by observing competent observations. Results of simak, libat, cakap methods are described qualitatively. The results show that there are some different language variations with their various factors. Language variations began to be used along with the development of their age, so the acquisition of the language has begun to show its uniqueness. The level of speech used is not used to fulfill the rules in force, such as using polite language when talking to their parents. This situation is very possible to occur due to environmental factors that do not support the use of speech levels at the time of speaking. Language variation of formal and informal can already be distinguished by speakers both consciously or not. The speech form is marked by the form of words and sentences that are concise, such as in the language spoken in a child’s environment. Some languages that emerge and are used in daily life, are Indonesian, Sundanese, English and Arabic and they make speakers have a lot of vocabularies. Serious revitalization is needed to protect local language lost. Keywords: language variation, speech, multilingual, language lost